On the Logic of Islamic Feminism: A case study of Minangkabaunese Matrilineality - Firdaus, Qusthan Abqary Hisan (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2024)
This article aims to seek (1) a new meaning of Islamic feminism and (2) its logical structure whether traditional or modern in its nature. I will examine Etin Anwar’s distinction between ‘Islamic feminism’ and ‘Muslim feminism’ and discuss the potential of self-ownership for developing arguments in favor of gender justice. While Anwar’s definition of Islamic feminism excludes male feminists in such a way, I argue that it is not strategic for gender justice, and it would be necessary to adopt self-ownership into the discourse of Islamic feminism instead. This suggestion manifests in the Minangkabau matrilineal setting, in which case men share their self-ownership with their wives, mothers, and sisters due to the institution of bundo kanduang. As a consequence, Minangkabaunese Muslim men shoulder some extra filial duties but enjoy nothing from the inheritance division. I also conducted several in-depth interviews with some experts concerning this issue. The upshot is that Islamic feminism should be inclusive of male feminists, and it should pay attention to the modern logic of dialetheia instead of the traditional logic.